Sustainable freight forwarding – inland navigation - David, Andrej (Cognitive Sustainability, 2024)
Inland navigation plays a crucial role in goods transport, facilitating the movement of goods via rivers and canals. Sustainability in Goods transport involves reducing environmental impact, promoting social responsibility, and enhancing efficiency. Sustainability in goods transport includes optimising transportation routes, investing in fuel-efficient vehicles, and promoting alternative fuels. Green technologies such as GPS tracking and route optimisation software can improve efficiency. Encouraging sustainable packaging materials and carbon offsetting can further reduce environmental impact. Inland navigation can be greener by adopting alternative fuels, improving vessel efficiency, and optimising routes. Maintenance and modernisation of infrastructure, environmental protection measures, and modal shifts from road transport also contribute to sustainability. Various factors influence the performance of inland navigation, including infrastructure, water levels, vessel characteristics, regulations, economic conditions, technological advancements, environmental factors, and social considerations. Integrating sustainable practices and addressing these factors can lead to a more environmentally friendly and efficient goods water transport system. This paper investigates the connections between inland goods transport and sustainability, identifying the main factors. Some basic statistics were collected and analysed to show the performance of inland navigation. The analysis showed that inland navigation is very diverse in Europe, Western Europe is more developed than Eastern European countries. In conclusion, it can be stated that many factors influence the development of Eastern European inland navigation.